Competence Drives Interest or Vice Versa? Untangling the Bidirectional Relationships between Creative Self‐Efficacy and Intrinsic Motivation for Creativity in Shaping Employee Creativity - Chen, Tingting; Kim, Tae‐Yeol; Gong, Yaping; Liang, Yongyi (Journal of Management Studies, 2025)
Research has examined creative self‐efficacy and intrinsic motivation for creativity as important antecedents to employee creativity, but little is known about how the two antecedents influence each other to foster employee creativity. This study proposes two theoretical possibilities. First, by enhancing resilience, creative self‐efficacy can promote intrinsic motivation for creativity, which in turn boosts employee creativity. Task difficulty further strengthens creative self‐efficacy's effect on intrinsic motivation for creativity and employee creativity (via resilience). Second, by fostering creative process engagement, intrinsic motivation for creativity can promote creative self‐efficacy, which in turn boosts employee creativity. Task variability further amplifies the effect of intrinsic motivation for creativity on creative self‐efficacy and employee creativity (via creative process engagement). Results from two experiments and two field studies largely supported the hypothesized relationships. We extend the creativity literature by untangling the interrelationships between creative self‐efficacy and intrinsic motivation for creativity in shaping employee creativity.